Analysis of Persuasive Narrative Design in Social Media Content for Early Childhood Development - Nilna Mar’atul Fauziyyah; Muniroh Munawar; Perdana Afif Luthfy (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
The development of digital media has made YouTube one of the most frequently accessed platforms by young children. In the context of Early Childhood Education (ECE), the design of persuasive narratives in digital content is a critical aspect because children are still in the imitative development stage and are not yet able to critically filter information. This study aims to analyze the design of persuasive narratives in YouTube social media content and its relationship to the growth and development of young children. The study employed a descriptive qualitative approach using content analysis, a Google Form survey, and in-depth interviews with parents. Research data were obtained from the analysis of 30 children’s YouTube videos and in-depth interviews with 8 parents of young children. The analysis was based on four indicators: processing fluency, emotional engagement, narrative structure, and ethical value. The results showed that 17 videos (56.67%) fell into the “appropriate” category, as they featured simple language, coherent narrative structure, positive emotional engagement, and moral values that support children’s development. Meanwhile, 13 videos (43.33%) were classified as “inappropriate” because they emphasized visual stimulation, impulsive behavior, and consumerist elements. This study demonstrates that the design of persuasive narratives in digital media plays a role in the language, behavioral, and social-emotional development of young children.